Post-spray treatment of HA coating using laser - Beh, Pang Yoke. (2008)
Hydroxyapatite (HA) coatings on orthopedic prostheses have the surface characteristics that allow bone to grow into the surface pores and thus reduce the recuperation period of patients.'I,2] Thermal spray is a popular technique used for coating HA on orthopaedic prostheses. It is a fast and easy coating technique as compare to other techniques like chemical vapor deposition (CVD). However, one of the problems in thermal spray of HA onto orthopedic prostheses is the phase change of HA during the coating process.131 The pure and crystalline HA starting powder, which is bioactive, undergo thermal decomposition to amphorous calcium phosphate during the thermal spray process.'41 Amphorous calcium phosphate is highly resorbable and is therefore not desirable.'51 A pulsed mode Nd:YAG laser was used in this project to perform post-spray heat treatment of the plasma sprayed HA coating. Purpose of heat treatment being transforming amphorous calcium phosphate to crystalline phase. Laser heat treatment has the advantage of being a rapid process with minimal amount of distortion on the part. Scanning electron microscopy observation of the laser treated coating revealed that crack network and micro-pores on the coating increases with increasing laser power. Increasing the laser power used on coating also increases the crystalline HA phase composition. Highest transformation of amphorous calcium phosphate to crystalline HA was obtained when a 5.5 J laser power was used on the coating however together with the highest crack network. Some compromise is therefore necessary between getting higher HA crystallinity and coating integrity.